We can write 1/4 as 2^(-2), so the equation becomes:
8^m = 2^(-2) - 2^(3m)
We know that 8 can be written as 2^3, so we can substitute that in:
(2^3)^m = 2^(-2) - 2^(3m)
Simplifying the left-hand side using the power of a power rule:
2^(3m) = 2^(-2) - 2^(3m)
Now we can combine the two terms on the right-hand side, since they have the same base:
2^(3m) = 2^(-2-3m)
Using the rule that a^(−n) = 1/a^n:
2^(3m) = 1/2^(2+3m)
Multiplying both sides by 2^(2+3m):
2^(5m+2) = 1
Now we can solve for m by taking the logarithm base 2 of both sides:
5m + 2 = log2(1)
Since log2(1) = 0, we get:
5m + 2 = 0
Solving for m:
m = -2/5
Therefore, m = -0.4.
If 8^m=1/4 -2^3m. Find m
3 answers
AAAaannndd the bot gets it wrong yet again!
2^(3m) = 2^(-2-3m)
2^(6m+2) = 1
6m+2 = 0
m = -1/3
2^(3m) = 2^(-2-3m)
2^(6m+2) = 1
6m+2 = 0
m = -1/3
My apologies for the mistake in my previous response. You are correct that the equation simplifies to:
2^(3m) = 2^(-2-3m)
Taking the logarithm base 2 of both sides, we get:
3m = -2-3m
Simplifying and solving for m:
6m = -2
m = -1/3
Thank you for bringing this to my attention.
2^(3m) = 2^(-2-3m)
Taking the logarithm base 2 of both sides, we get:
3m = -2-3m
Simplifying and solving for m:
6m = -2
m = -1/3
Thank you for bringing this to my attention.